The conceptual metaphor of Valor in the language and imagery of The Houghton Shāhnama - Kamelia Kakoeian,; Afsaneh Kamran (مطالعات زبانی و بلاغی)
In Shāhnama, valor is a fundamental and extensive concept, interlinked with other notions such as wisdom, nobility, warriorship, courage, and reputation. This article aims to examine how the concept of valor is linguistically and visually expressed in Shāhnama; what conceptual metaphors has Ferdowsi employed to elucidate the concept of valor in his poetry, and what techniques has the miniature artist utilized to visualize these metaphors? Has the artist merely adhered to the text or employed creative approaches to convey this concept? To answer these questions, the research adopts George Lakoff and Mark Johnson's conceptual metaphor theory as its theoretical framework. The miniatures are selected from the Houghton (Tahmāsebi) Shāhnama, and their analysis is conducted using Kress and van Leeuwen's social semiotic approach to visual analysis. The findings indicate that, in addition to employing conventional elements such as the appearance of actors, composition, information value, framing, and salience, the miniature artist has utilized elements of performance like participant presence, scene requirements, and vector types to create action. Furthermore, relational elements such as point of view, distance, and contact have been used to depict conceptual metaphors of valor. In some of these images, the artist has been innovative in representing these metaphors, sometimes aligning with the overall narrative and sometimes diverging from it. Techniques such as salience, composition, and framing have been employed to augment and intensify the meaning of heroic metaphors in the miniatures.